Short-term and long-term survival outcomes for transrectal specimen extraction after laparoscopic right hemicolectomy: a propensity-score matching study - ReDati, DaRebai; Li, Weikun; Jiang, Yujuan; Yang, Xinhui; Lei, Cheng; Wang, Haijiang; Liang, Jianwei (Frontiers in Oncology, 2024)
Background Natural orifice specimen extraction surgery (NOSES) has been widely applied to the treatment of colorectal cancer. This study aim to investigate the short-term and survival outcomes of transrectal specimen extraction after laparoscopic right hemicolectomy. Methods From January 2016 to December 2021, a total of 166 consecutive patients with right colon cancer who underwent laparoscopic right hemicolectomy in Cancer Hospital of Chinese Academy of Medical Sciences and Beijing Hospital were identified. Baseline data, perioperative parameters, anal function, inflammatory indicators and survival outcomes were collected and compared. Results Totally, 24 patients who underwent transrectal NOSE were matched with 24 patients who received conventional laparoscopic surgery (LAP). Patients in NOSES group had a significantly lower incidence of incision infection (0 vs 20.8%, P=0.048), faster recovery of gastrointestinal function (2.1 vs 3,1 days, P=0.032) compared with those in LAP group. In addition, patients in the NOSE group experienced significantly less postoperative pain on POD1 (2.3 vs 4.4, P<0.001), POD3 (2.1 vs 3.9, P<0.001), and POD5 (1.7 vs 2.8, P=0.011). Regarding to anal function 6 months after surgery, no significant difference was observed in Wexner incontinence scale (9.8 vs 9.5, P=0.559) between the two groups. In terms of indicators of the inflammatory response, there were no significant differences in body temperature, neutrophils, and PCT levels between the two groups. However, CRP levels in the NOSES group on POD 3 (6.9 vs 5.1 mg/L, P=0.016) and POD 5 (3.8 vs 2.6 mg/L, P=0.027) were significantly higher than in the LAP group. With regarded to survival outcomes, patients in the NOSES group were similar to those in the LAP group for 3-year OS (100% vs 91.2%, P=0.949), 3-year DFS (86.2% vs 84.8%, P=0.949), and 3-year LRFS (94.2% vs 88.7%, P=0.549). Conclusion For total laparoscopic right hemicolectomy, transrectal NOSE is effective and safe, and associated with lower incidence of wound infection, less pain, faster recovery, and similar survival outcomes compared to conventional laparoscopic surgery.